2021
DOI: 10.1108/jrme-06-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

Profiting from innovation in the aftermath of an economic crisis

Abstract: Purpose The aim of this paper is to present systematically a variety of benefits from innovating in response to an economic crisis. Design/methodology/approach This is a conceptual paper that draws on prior conceptual and empirical studies, especially the innovation-based view of firm performance. Findings Many firms have cut their innovation expenditures in response to the COVID-19 crisis. However, the financial crisis in 2008/2009 has shown that these short-term cost savings may have severely negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Frugal innovation can be incentive that determine enterprises to redesign processes and adopt rapid decision making. Digital business models and can help companies surpass difficulties and develop frameworks that increase their competitive advantage (Dabic et al, 2022;Jha, 2021;Lichtenthaler, 2021;Kronblad & Pregmark, 2021). Entrepreneurs and usually small and medium businesses have been the most affected by the pandemic and the results show that a rapid decision-making process and adoption of agility can help solve better the problems encountered.…”
Section: Resultsmentioning
confidence: 99%
“…Frugal innovation can be incentive that determine enterprises to redesign processes and adopt rapid decision making. Digital business models and can help companies surpass difficulties and develop frameworks that increase their competitive advantage (Dabic et al, 2022;Jha, 2021;Lichtenthaler, 2021;Kronblad & Pregmark, 2021). Entrepreneurs and usually small and medium businesses have been the most affected by the pandemic and the results show that a rapid decision-making process and adoption of agility can help solve better the problems encountered.…”
Section: Resultsmentioning
confidence: 99%
“…Crisis and extreme conditions of high uncertainty (e.g. COVID-19 pandemic) in the contexts of MEI are receiving an increasing interest among researchers in the field (Eggers, 2020; Garcia et al , 2021; Lichtenthaler, 2021; Miles et al , 2016; Morrish and Jones, 2020; Pidduck and Clark, 2021).…”
Section: Progressmentioning
confidence: 99%
“…The work of Lichtenthaler (2021) has identified that with many organizations which survived the economic effects of the COVID-19 pandemic turned to budget cuts within innovation and R&D departments in order to free up resources to shore up other parts of the organizations. Innovation is often considered a necessary but not essential element of an organization, usually due to its speculative working ethos of looking for potential products or services, and the fact that any boost to revenue comes when an idea has been moved into a realized product or service.…”
Section: Cutting the Necessarymentioning
confidence: 99%
“…Innovation is often considered a necessary but not essential element of an organization, usually due to its speculative working ethos of looking for potential products or services, and the fact that any boost to revenue comes when an idea has been moved into a realized product or service. Lichtenthaler (2021) has categorized innovation within organizations into two "orders":…”
Section: Cutting the Necessarymentioning
confidence: 99%
See 1 more Smart Citation